IDENTITAS AKULTURASI ARSITEKTUR LOKAL (BANTEN) DAN NON-LOKAL (MODERN) PADA PEDOMAN PERANCANGAN GEDUNG PENDOPO BUPATI SERANG - Saga Ichsan, Pilar; Salura, Purnama; Fauzy, Bachtiar (Jurnal Riset Arsitektur, 2022)
Abstract - Government buildings should have a symbolic value that represents the area. The development of architecture in an area influences the development of the culture of the region, with the abandonment of the element of the architectural locality over time the element of the locality will become extinct. Based on these problems and phenomena, it produces quite important issues especially the acculturation of government buildings that can characterize the locality of a place. So that the research conducted is very important to answer how to produce local and modern concepts that are appropriate to the Serang Regent building design that characterizes the local socio-cultural context of the people of Banten. The purpose of this study was to obtain design guidelines and design simulations in realizing the acculturation identity of local architecture (Banten) and non-local (modern) in the design of the Serang Regent's Pendopo building. The theory applied in this study refers to (1) the archetypes theory in architecture and (2) the ordering principle theory in architecture. Besides that, the methods used in this research are descriptive, qualitative and interpretative that can be used in conducting studies and in–depth searches of the object, the precedent studies that are Pontianak mayor government building and Solok regent government building. The results of the analysis of the object of the study of precedents against the theory with the method that has been described are to obtain specific design guidelines for the Serang Regent's Pendopo building. This research is expected to provide benefits to the community on the importance of localities in preserving and building local culture and architecture and can add to the wealth of existing architectural knowledge for both academics and practitioners and make a positive contribution to local governments for making regional regulations. Keywords: Identity, Acculturation, Architecture, Local, Non – Local, Banten.